A Simple Spectrophotometric Method for Determination of Propoxur - Harikrishna, V.; Naidu, N.V.S. (Asian Journal of Chemistry, 2010)
A new spectrophotometric method for the determination of propoxur is described, based on coupling the hydrolysis product with diazothed p-chloroaniline to give an orange coloured compound having an absorption maximum at 459 nm. Beer's law is obeyed over the concentration range 0.5-10 ppm.